Detection of tox A gene in Pseudomonas aeruginosa that isolates from different clinical cases by using PCR. - Al-Shwaikh, Rana M. Abdullah; Alornaaouti, Abbas Falih (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2018)
Current study obtained (75) isolate of Pseudomonas aeruginosa collected from different cases included : 28 isolates from otitis media, 23 isolates from burn infections, 10 isolates from wound infections, 8 isolates from urinary tract infections and 6 isolates from blood, during the period between 1/9/2014 to 1/11/2014 The result revealed that the tox A gene was present in 54 isolates (72%) of Pseudomonas aeruginosa. The gel electrophoresis showed that the molecular weight of tox A gene was 352 bp. The result shows 17 isolates (60.71%) from otitis media has tox A gene, 18 isolates (78.26%) from burn followed by 8 isolate (80%) from wound infection and 5 isolates (62.5%) from urinary tract infection , finally 6 isolates (100%) from blood have this gene.